Impact of Indigenously Prepared Therapeutic Food for Children with Acute Malnutrition at Nutritional Rehabilitation Center - Joshi, Prakash; Yadav, Jeet Narayan; Gautam, Rabin (Birat Journal of Health Sciences, 2020)
Introduction Malnutrition in all its forms remains unacceptably high across all regions of the world especially in developing countries.1 Malnutrition impairs physical and mental growth of child as well as increases morbidity and mortality depending upon the degree of malnutrition. There is paucity of literature regarding incidence of malnourished children and outcome of nutritional rehabilitation in a hospital based setting, in western Nepal. Objective: The objective of the study was to find the incidence and type of acute malnutrition and their outcome in Nutrition Rehabilitation Home (NRH). Methodology: This is a descriptive cross-sectional study conducted at nutrition rehabilitation center of Rapti Subregional Hospital (RSRH), in which all children between 6 to 59 months of age with severe and moderate acute malnutrition (SAM and MAM) admitted from July 2017 to June 2018 were enrolled. Variables like age, sex, length/height, weight, weight gain during stay, duration of stay, Z score of weight for length/height (WLZ/WHZ), weight for age (WAZ) and Height for age (HAZ) were recorded. Outcome were recorded as cured, recovered, defaulted, primary failure and referred. Data entered in excel and analysis was performed by using SPSS 20 and the results were expressed as number, proportion vertion and average. Result: Among 105 patients admitted, 90 (85.71%) were below the age of 24 months with mean age of study population being 16.82 months and male female ratio M:F of 1.14:1. Proportion of children with SAM and MAM was 59(56.19%) and 46(47.61%) respectively. Among 75 (71.42%) stunted children, 51(68%) were severely stunted. Among the study populations cure rate was 30.47% (32 person), recovery rate 24.76% (26 person). Defaulter rate was 7.6% (8 person) and primary failure were 18.09% (19 person) referred were 1.9% (2 person). No mortality occurred in the rehabilitation center. Average weight gain for the study population was 6.56 mg/kg /day. Average duration of stay was 21.83 days. Conclusion: This study highlights the integral role of locally prepared therapeutic diet besides standardized care provided at nutrition rehabilitation center in order to combat malnutrition, a major problem in the developing world. To sustain the achievements and prevent relapse, there is a need to integrate the services at nutrition rehabilitation center with the community-based therapeutic care as well.